Safety assessment of the process Plastrec, based on Polymetrix pellet technology, used to recycle post‐consumer PET into food contact materials. (30th April 2021) - ,; Lambré, Claude; Barat Baviera, José Manuel; Bolognesi, Claudia; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Mengelers, Marcel; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Plastrec (EU register number RECYC181), which uses the Polymetrix pellet technology. The input is hot washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, mainly bottles, with no more than 5% PET from non‐food consumer applications. The flakes are extruded into pellets, crystallised and subsequently decontaminated in a ■■■■■ solid‐state polycondensation (SSP) reactor under high temperature and inert gas flow. The recycled pellets are intended to be used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature, with or without hotfill. The Panel concluded that the dossier does not satisfy the requirements of the EFSA guidelines, because the data and clarifications provided by the applicant do not allow an adequate evaluation of the decontamination efficiency of the process. Consequently, the CEP Panel concluded that the applicant has not demonstrated that the recycling process is able to reduce contamination of the PET flake input to a concentration that does not pose a risk to human health.